Efficient DNA-Free Protoplast Gene Editing of Elite Winegrape Cultivars for the Generation of Clones With Reduced Downy Mildew Susceptibility - Christine Böttcher; Debra McDavid; Angelica M. Jermakow; Patricia Iocco-Corena; Nayana Arunasiri; Suzanne M. Maffei; Paul K. Boss (Australian Journal of Grape and Wine Research)
Conclusions: This study has demonstrated that a relatively simple and robust protoplast isolation, DNA-free protoplast transfection and plant regeneration workflow can be used to efficiently produce nontransgenic, diploid, edited clones with desired phenotypes of four elite winegrape cultivars, including the highly recalcitrant Cabernet Sauvignon.